STRUCTURAL FEATURES OF THE GOLOVANEVSK SUTURE ZONE CRYSTALLINE BASEMENT IN THE YATRAN RIVER BASIN BASED ON TECTONOPHYSICAL DATA - Mychak, S.; Kurylо, S.; Murovskaya, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents the results of tectonophysical study of the upper part of the Earth's crust of the Yatran block of the Golovanevsk suture zone within the Ukrainian Shield, performed in 2016 in the basin of the middle and lower reaches of the Yatran River. The purpose of the work was to study the deformation of rocks and restore paleostresses for the subsequent construction of the geodynamic model of the earth's crust of the Pobuzhsky ore mining district. Field tectonophysical studies were performed using the structural-paragenetic method for I-II depth levels. To construct stereograms of linear structures and fracturing of rocks, the Stereonet program was used. The obtained data made it possible to clarify the tectonic history and mechanisms of deformation of the Yatran block. The obtained results allow to conclude that the studied linear and banded structure of the rocks was formed at the early stages of right and left strike-slip deformation within the Golovanevsk suture zone, after that a diagonal systems of brittle cracks were formed at the stages of W-E and N-S compression. The early crystallization cleavage and schistosity, linear and banded texture of the rocks were formed at the early stages of the right- and left-shear deformation of the Golovanevsk suture zone. The milonite monoclines and structural textural elements of fault zones are widely developed in zones of maximal shear deformations (Shear zone). The migmatite-granite igneous monoclines with potash feldspar mineralization are widely developed in the Early Proterozoic Talnovsk fault zone. Plagiomigmatitic monoclines are developed in the Neo-Archaic Emilovsk fault zone. Later, a diagonal system of cracks was formed at the stages of sublatitudinal compression and extension. The youngest crack system of the Yatran block was formed at the stages of the north-west – south-east and north-east – south-west compression-extension. Thus, the results of work return the researchers to the study of rock fracturing with the aim of the investigation of the geodynamic evolution. This article shows a structural-petrophysical and tectonophysical schematic base of the geological-structural map of the surface of the crystalline basement, on which geological-petrophysical taxons and structural-kinematic data on deformations of the upper part of the earth's crust of the studied region are displayed. The construction of a model of the stress-strain state of the earth's crust of the region is necessary for further geological-prospecting and engineering-geological researches.
Keywords: Ukrainian shield; Golovanevsk suture zone; deformations; stress fields; fault zones